Bolivia Financial Sector Notes : Assessing the Sector's Potential Role in Fostering Rural Development and Growth of the Productive Sectors - World Bank (Washington, DC, 2014)
Bolivia benefited from an overall favorable economic evolution in the last few years, supported by sound macro-economic indicators. Yet, economic growth was unevenly distributed between the sectors, with particularly extractive industries, construction and financial services showing higher real growth rates, while agriculture and manufacturing fell behind. This is an area of concern for the government which-as manifested in the new constitution-aims to foster a more balanced and equitable growth. In its reform measures, it places a particular focus on developing the rural areas, in which a large share of the indigenous population lives, and on the productive sector (agriculture, forestry, manufacturing and extractive), which provides the livelihood for a substantial number of poor people. This paper aims to contribute to the discussion and on-going reform efforts by providing an evaluation of the role the financial system could play for enhancing growth in rural areas and the productive sector without threatening the sector's stability. It also endeavors to update the Bank's knowledge on the financial sector, assess its current role and recent developments, and determine possible vulnerabilities as well as core bottlenecks for the outreach to underserved segments of the population and economy. However, the government needs to strike a fine balance in its policy measures to foster outreach and credit in order to not unduly lower the profitability in the financial sector, jeopardize the quality of the loan portfolio and as a result introduce vulnerability in an otherwise sound system. In particular, the strong push towards financing of the productive sector at comparatively low interest rates, can lead to over-indebtedness of the clients or a deterioration of the repayment culture, if lending institutions expanding their loan portfolios do not maintain (or introduce) prudent lending